Fabricating Spatially-Varying Subsurface Scattering - Dong, Yue; Wang, Jinpeng; Pellacini, Fabio; Tong, Xin; Guo, Baining; Lin, Steve (Material Appearance Modeling: A Data-Coherent Approach, 2013)
Many real world surfaces exhibit translucent appearance due to subsurface scattering. Although various methods exist to measure, edit and render subsurface scattering effects, few solutions exist for manufacturing physical objects with desired translucent appearance. In this chapter, a complete solution is presented for fabricating a material volume with a desired surface BSSRDF. Layers are stacked from a fixed set of manufacturing materials whose thickness is varied spatially to reproduce the heterogeneity of the input BSSRDF. Given an input BSSRDF and the optical properties of the manufacturing materials, the system efficiently determines the optimal order and thickness of the layers. This approach is demonstrated by printing a variety of homogeneous and heterogeneous BSSRDFs using two hardware setups: a milling machine and a 3D printer.